Ecological Momentary Assessment and Intervention Principles for the Study of Awake Bruxism Behaviors, Part 2: Development of a Smartphone Application for a Multicenter Investigation and Chronological Translation for the Polish Version - Osiewicz, Magdalena A.; Lobbezoo, Frank; Bracci, Alessandro; Ahlberg, Jari; Pytko-Polończyk, Jolanta; Manfredini, Daniele (Frontiers in Neurology, 2019)
Objectives: The aim is to describe the process of translating the smartphone application BruxApp into Polish within the context of an ongoing multicenter project on awake bruxism (AB) epidemiology. Material and Methods: An ongoing cooperation involving 11 universities is based on the adoption of the smartphone-based EMA protocol to collect real time report of AB behaviors in the natural environment. The English version of BruxApp is adopted as a template for the multi-language translation, according to a step-by-step procedure led by mother-tongue experts in the field. A dedicated web platform for translation (viz., POEditor) is used. The process of translation into Polish is here described as an example. Results: There are two software versions available, viz., BruxApp and BruxApp Research. For both versions, back translation from Polish to English was performed to verify the accuracy of the translation procedure. The validity of the translation has been confirmed by the perfect agreement between the original and back-translated English versions, and the Polish version of BruxApp can thus be introduced in the clinical and research setting to get deeper into the study of AB epidemiology in Poland. Conclusions: As far as clinical studies are concerned, the described strategy to record data can be very useful – patients can acknowledge their habits, monitor changes over time and implement remedial measures. In the field of research, BruxApp makes it possible to collect and store a huge amount of data about the epidemiology of different forms of awake bruxism, both at the individual level and at the population level.